Grammar And Context Based Approach For Identification And Translation Of Proverbs Using Trie-Based Ontology - Shaikh, Naziya (International Journal of Computer Sciences and Engineering, 2025)
Most current machine translation systems for translation from English to regional Indian languages ignore the presence of idioms in the text or return the exact literal meaning of the phrase in another language which loses the essence of the proverb. The main issues that arise include timely detection of the proverbs from a given paragraph and the separate processing required for translations of idioms into other languages. This paper presents a combination of natural language grammar-based approach and context-based approach towards detection of idioms in given English text and further presents a trie-based ontology that can be used to translate proverbs into regional languages. The grammar-based approach involves parsing English sentences and identifying the parts-of-speech tags and determining statistically the probability whether the given sentence is a proverb using certain grammar-based rules applicable for only proverbs. The context-based approach classifies and compares keywords in the proverbs and the keywords present in remaining part of the paragraph. Based on the combination of these two approaches, the proverb can be determined with better accuracy. For quick translation of detected proverbs into regional languages, keyword based priority search can be implemented on previously developed trie-based ontology using parts-of-speech tags